Psychological distress among middle-aged adults with Diabetes Mellitus: findings from the Indonesia national population health survey (Riset Kesehatan Dasar, Riskesdas 2018) - Marisa Syavitri Dilaga; Aimi Nadira Mat Ruzlin; Xin Wee Chen (Discover Social Science and Health)
Abstract Objectives Due to social challenges and difficulties adapting to their treatment, middle-aged adults with Diabetes Mellitus (DM) are at a greater risk for developing psychological distress. This study aimed to determine the prevalence of psychological distress and its determinants among middle-aged adults with DM in Indonesia. Methods A national population-based health survey (Indonesian Riset Kesehatan Dasar, Riskesdas) involving 1,017,290 respondents was conducted in 2018. The present analysis included all middle-aged adults (45–60 years old) with DM. Information regarding socio-demographic, clinical-related, social-behavior, and psychological distress status using the World Health Organization Self-Reporting Questionnaire-20 (SRQ-20) was abstracted from the database. Logistic regression analyses were applied. Results The prevalence of psychological distress among middle-aged adults with DM was 18.3% (95% CI 13.7, 22.9). The participants' mean (standard deviation) age was 53.0 (4.44) years. They were predominantly female, had low education levels, were employed, married, and lived in urban areas. Multiple logistics regression analysis demonstrated nine factors associated with psychological distress—sex, education, occupation, marital status, home location, body mass index, comorbidities, DM regimen, and smoking. Conclusions Multiple factors were significantly associated with psychological distress. This lays the groundwork for future policymakers to strongly recommend integrating mental health screening at DM diagnosis and on a yearly basis, prompt referral, early interventions, and the delivery of targeted mental health education to the high-risk populations in the effort of prevention and control of psychological distress among middle-aged adults with DM.